Sosialisasi Tentang Manfaat Sari Kacang Hijau Terhadap Kesehatan Reproduksi Dan Anak - Rio Jenita Sipayung; Rianita Siagian; Hanry Anta Lesmana; Jeanika Pinem (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
The maternal mortality rate (MMR) in Indonesia remains high, with many cases linked to pregnancy complications associated with iron deficiency anemia (IDA). Anemia has widespread effects on women’s reproductive health and child development, including decreased immunity, cognitive impairment, and increased risk of premature birth. One promising nutritional intervention is the consumption of mung bean extract, which is rich in iron. This community service activity aimed to improve public knowledge and skills regarding the benefits of mung bean extract for women's reproductive health and child nutrition. The program involved educational sessions and practical demonstrations delivered to residents in the target area, with active participation from local leaders and community members. The results showed increased awareness and motivation among the participants to consume mung bean extract regularly. The enthusiasm demonstrated by the community indicates the effectiveness of this outreach in raising awareness about the importance of simple nutritional interventions to prevent anemia and improve maternal and child health. It is hoped that this activity can be sustained as a promotive and preventive public health effort.